The application of decomposed theory of planned behavior on participation in Islamic microfinance from Malaysian’s perspective / Izjuni Irdina Izahar - Izahar, Izjuni Irdina (2019)
The potential of Islamic microfinance does not only restrict to the need of meeting demands, but also to integrate the Islamic social principle to care for the less fortunate with microfinance’s ability in providing financial access to the poor. As the religious values contradict to the operations of conventional MFIs, large numbers of Muslim communities have been quite reluctant to participate in microfinance programmes. In this respect, Islamic MFIs may be a suitable alternative in countries where Muslims are predominant. Islamic microfinance is said to be lagging behind the other conventional microfinance since there is a huge untapped Islamic microfinance where there is only 10.9% penetration into the market. The main objective of this study is to examine the factors that affect Malaysian customers’ perspective in participating in using Islamic microfinance. This study adopts a research framework of Decomposed Theory of Planned Behaviour. This paper used primary data collected by self-administered questionnaires involving a sample of 166 respondents from Islamic microfinance users. This study revealed that among eleven beliefs, only two of them are not significant which are awareness of clients and their attitude towards using Islamic microfinance and the normative beliefs of others affected clients’ subjective norms to participate in Islamic microfinance. The data were collected from existing clients of Islamic microfinance. Thus, behavioural intention is excluded from the study. The sample size of the study and also the scope of the study is limited since it only focus in peninsular Malaysia. For future research study, it may be broaden to include behavioural intention as the variables and also to broaden the scope of the study. The finding of this study may help Islamic microfinance providers to better manage by focussing on relative advantage and behavioural control to build client relationships.